Green supply chain management and firms' performance: Understanding potential relationships and the role of green sourcing and some other green practices - Jabbour, Ana Beatriz Lopes De Sousa [UNESP]; Frascareli, Fernanda Cortegoso De Oliveira [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (Elsevier, 2015)
This study examines how the adoption of green supply chain management (GSCM) practices, including green sources, affects environmental and operational performance indicators. A multiple-case study was conducted using large Brazilian firms that have achieved particular success in their sectors and that occupy high positions in important rankings of corporate sustainability. The results of the study indicate that the GSCM practice of internal environmental management has the greatest positive effect on environmental performance indicators, and that the GSCM practice of cooperation with customers has the greatest positive effect on operational performance indicators. Thus, if a company aims to improve environmental performance (EP), it may create procedures and programs based on the environmental management system and adopt cleaner production initiatives. If a company intends to improve its operational performance (OP), it may respond to audits, improve information exchange between companies and clients and build research and development (R&D) areas to promote environmental innovation.
Keywords: Environmental performance; Green sourcing; Green supply chain; Operational performance; Sustainable operations management; Sustainable supply chain